Picturing Crusoe’s Island: Defoe, Rousseau, Stothard - Lipski, Jakub (Porównania, 2019)
This article analyses Thomas Stothard’s illustrations of Robinson Crusoe arguing that the heightened interest in and appreciation of nature in Stothard’s set should be seen in the context of sentimental readings of Daniel Defoe’s Robinson Crusoe, which, unlike the original, recognised the benefits to a solitary life in natural surroundings. The article traces some fundamental steps in this change of paradigm, first by showing Defoe’s reticence about natural beauties, and then by juxtaposing Stothard’s contribution with how J. J. Rousseau read and interpreted Robinson Crusoe.